High-Order-Harmonic Generation and Ionization from H2 by Time-Dependent Density-Functional Theory (Journal of Atomic and Molecular Sciences, 2017)
The ionization and high-order harmonic generation (HHG) of a hydrogen molecule in an ultra-shortintense laser are investigated by using the time-dependent density functional theory (TDDFT). Our numericalresults show, the higher ionization probability and lower cutoff energy of harmonic emission compared withthose from the time-dependent Schrodinger equation (TDSE), which is caused by the smaller ionizationenergy from TDDFT. The disparities of the HHG transient behavior and the attosecond pulse are alsodiscussed.
Keywords: time-dependent density functional; high-order harmonic generation; attosecond.